COMPARISON OF IN VITRO DIGESTIBILITY OF DIETS CONTAINING SUBABUL PLANT AS FODDER IN DROMEDARY CAMEL AND COW - Tahereh Mohammadabadi; Abdul Raziq Kakar (Exploratory Animal and Medical Research, 2019)
The aim of this study was to compare in vitro digestibility of diet containing Subabul (Leucaena leucocephala) at blooming stage in cow and dromedary camel. The experimental diets were including 0, 25, 50 and 100% of Subabul branches as a replacement of Alfalfa (Medicago sativa). The ingredients of diets were Alfalfa, wheat straw, corn silage, corn, barely, bran and mineral-vitamin supplement by a ratio of concentrate and forage at 50:50. Rumen fluid was taken from fistulated cow and dromedary camels and in vitro digestibility of experimental diets was determined. The obtained data were analyzed in a split plot design. The lowest digestibility of dry matter in dromedary camel (73.1%) and cattle (71.9%) was found in the treatment containing 100% of Subabul (p<0.05). But digestibility of natural detergent fiber (NDF) and acid detergent fiber (ADF) of diets containing different levels of Subabul instead of Alfalfa were not different in cow and camel (p>0.05). Digestibility of NDF and ADF in the treatment containing 100% Subabul in the cattle were 70.36 and 68.21%, respectively, and in the dromedary camel were 71.19% and 69.02%, respectively (p<0.05). Treatments containing 50 and 100 % Subabul (74.38 and 70.37%) had the lowest dry matter digestibility (p<0.05). The ADF digestibility in treatments containing 50 and 100% Subabul in compared with control treatment was 72.4 and 67.6 vs 73.5 %, respectively, and NDF digestibility was 72.45, 69.65 and 75.33 % in treatments containing 50 and 100% Subabul and control, respectively (p<0.05). As per the result, the digestibility of DM, NDF and ADF of Subabul were not different between cow and dromedary camel (p>0.05).The result of these experiments showed that in vitro digestibility of 50 % Subabul instead of Alfalfa in diet of cow and camel was better than other levels, therefore it can be used in cow and dromedary camel nutrition.